What Makes Remote Teams Work: Exploring The Factors Behind Effective Virtual Collaboration - Resmini, Komang Tri; Mahyuni, Luh Putu; Supriyadinata Gorda, Anak Agung Ngurah Eddy; Martini, Ida Ayu Oka (Amkop Management Accounting Review (AMAR), 2025)
This study aims to understand the dynamics of team management in this context in depth, including how team interactions are formed and how team effectiveness is maintained in a virtual workspace. Using a qualitative approach, this study explore in-depth how team management is carried out in a remote work system, what challenges arise, and how team members interpret their experiences of working in a distributed manner. This research is expected to contribute not only to the theoretical aspects of human resource management but also to provide practical guidance for companies in building a more inclusive, collaborative, and adaptive remote work system to meet changing times. Based on the results of the analysis and discussion that have been carried out in this study, the following conclusions can be drawn: Teamwork is related to the existence of solidarity within team members who work together where they depend on each other for resources to achieve organizational goals. Teamwork is an association or group of individuals who depend on each other for tasks and shared responsibility for which the results of performance are very high compared to the results of work done by individuals.